Aspects of OMICs sciences in the neurobiology of aggressive human behavior (Research, Society and Development, 2024)
The understanding of human behavior is based on pathogenetic concepts, empirical therapies and neuropsychopharmacological approaches, involving neurotransmitters such as norepinephrine, dopamine, serotonin, and the treatment of underlying pathologies includes psychotropic drugs, antipsychotics and selective inhibitors, whose effectiveness has been limited, denoting the involvement of other pathways in the pathogenetic process. Studies based on omic sciences (molecular biology, metabolism, transcriptional factors, genetics and epigenetics) demonstrate several genes and genetic processes of DNA methylation and repair involved in the pathogenesis of these diseases. The aim of this article is to present a systematic review study on the main aspects of omics sciences that can contribute to the understanding of the molecular mechanisms of human aggressive behavior, given its presence in most psychiatric disorders. The molecular knowledge of these processes reveals an overlap of genetic and epigenetic foundations that can provide useful information for the study, diagnosis, prediction and therapeutic research of the mechanisms of human aggressive behavior.